Effects of emulsified kerosene nanodroplets on the entrainment of gangue materials and selectivity index in aphanitic graphite flotation. (1st November 2020) - Zhou, Shaoqi; Wang, Xuexia; Bu, Xiangning; Shao, Huaizhi; Hu, Yue; Alheshibri, Muidh; Li, Biao; Ni, Chao; Peng, Yaoli; Xie, Guangyuan
Highlights: Micron- and nano-droplets of emulsified kerosene were prepared. Nanodroplets enhanced bubble coalescence and froth drainage better. Nanodroplets inhibited entrained gangue and favored selective flotation of graphite. Abstract: In this study, kerosene emulsions with different average droplet sizes (700 nm, 854 nm, and 996 μm) were prepared to investigate their effects on the entrainment of gangue materials and the selectivity index in the flotation of aphanitic graphite. The calculation results based on Neethling and Cillers's model indicate that a decrease in the average droplet size of emulsified kerosene would result in a decrease in the entrainment of gangue materials, which corresponds to the observations of froth layer height, maximum water recovery rate, and bubble size in the top section of the froth zone. This may be ascribed to the enhanced collision probability between graphite particles and oil droplets, as well as the increased modified flotation rate constant compared to the micro-scale droplets. It is also noted that the selectivity index in graphite flotation increases as the average droplet size of kerosene emulsions decreases. This is largely due to the synthetic effect of the mitigated gangue entrainment and the intensified collision between graphite particles and oil droplets in the presence of nano-scale oil droplets.